Biological complications in patients with implant-supported dental restorations - Aćimović Tijana (Stomatološki glasnik Srbije, 2020)
Introduction Biological complications are the most common type of complications around dental implants. They appear in two forms, peri-mucositis and peri-implantitis. The aim of our research was to analyze the above-mentioned complications regarding the time elapsed from implantation and implant loading, as well as regarding the type of dental restoration. Material and methods 18 patients with self-reported complications were examined at the Department of Periodontology and Oral medicine, School of Dental medicine, University of Belgrade. Each patient filled an anamnestic questionnaire. Clinical examination, including photographic and radiographic documentation have been performed. Results Clinical examination included 18 patients and 97 implants in total (70% female patients and 30% male patients). The average time elapsed from implants placement was 7.5 years and the average from final dental restoration was 7 years. Periodontitis was diagnosed in 85% of the patients. Complications were more common among the patients with cement-retained restorations. Conclusions Due to the limitation of our study, we can assume that periodontal disease and cement-retained restorations are the risk factors for genesis and development of the complications around dental implants. The results of our study are in consent with data found in the literature, but in order to confirm these results it is necessary to perform analysis on a larger sample and with longer follow-up.